2005
DOI: 10.1002/zaac.200570055
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Dielectric Properties of the Perovskite LaMn0.5Co0.5O3–δ

Abstract: Polycrystalline samples of the charge ordered mixed oxide LaMn 0.5 Co 0.5 O 3Ϫδ (T CO ϭ 400 K) have been prepared by the nitrate decomposition method. These samples are biphasic, according to XRPD, and except one, oxygen defficient (δ ϳ 0.04-0.05). The study of the dielectric properties of these samples reveal that LaMn 0.5 Co 0.5 O 3Ϫδ displays a high dielectric constant, specially at room temperature and low frequencies. This εЈ r is seen to be strongly dependent on the particle size and not so much on the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 25 publications
2
23
0
Order By: Relevance
“…In this context, a previous and preliminary study from our research group on a sample with this stoichiometry and unknown degree of ordering revealed a very interesting high dielectric constant at room temperature (ε r ∼10 5 ) [14].…”
Section: Introductionmentioning
confidence: 96%
“…In this context, a previous and preliminary study from our research group on a sample with this stoichiometry and unknown degree of ordering revealed a very interesting high dielectric constant at room temperature (ε r ∼10 5 ) [14].…”
Section: Introductionmentioning
confidence: 96%
“…From an applied point of view, different cobalt compounds present interesting features in different applications as mixed conductors, materials for solid oxides fuel cells, thermopower applications, room-temperature ͑RT͒ ferromagnets, or magnetodielectric materials. [1][2][3][4] From a fundamental point of view, these oxides present complex behavior, magnetoresistance, intriguing metal-insulator transitions, superconductivity, spin-state transitions, charge order, etc. [5][6][7][8][9][10][11][12] The ability of cobalt ions in perovskite structure to present different spin states as a function of temperature, applied field, pressure, chemical tuning, etc., plays a major role in this richness.…”
Section: Introductionmentioning
confidence: 99%
“…CaMn7O12 polycrystalline materials were synthesized by the Pechini method 19 as published elsewhere [20][21][22][23] , using CaCO3 (Panreac, >98.6%) and Mn(NO3)2·H2O (Aldrich, >98%). 24 .…”
mentioning
confidence: 99%